Treatment of Active Crohn's Disease With Exclusive Enteral Nutrition Diminishes the Immunostimulatory Potential of Fecal Microbial Products - Kerbiriou, Caroline; Dickson, Caitlin; Nichols, Ben; Logan, Michael; Mascellani, Anna; Havlik, Jaroslav; Russell, Richard K; Hansen, Richard; Milling, Simon; Gerasimidis, Konstantinos (Inflammatory bowel diseases, 2024)
BACKGROUND: Exclusive enteral nutrition (EEN) is an effective treatment for active Crohn's disease (CD). This study explored the immunostimulatory potential of a cell-free fecal filtrate and related this with changes in the fecal microbiota and metabolites in children with active CD undertaking treatment with EEN. METHODS: Production of tumor necrosis factor α (TNFα) from peripheral blood mononuclear cells was measured following their stimulation with cell-free fecal slurries from children with CD, before, during, and at completion of EEN. The metabolomic profile of the feces used was quantified using proton nuclear magnetic resonance and their microbiota composition with 16S ribosomal RNA sequencing. RESULTS: Following treatment with EEN, 8 (72%) of 11 patients demonstrated a reduction in fecal calprotectin (FC) >50% and were subsequently labeled FC responders. In this subgroup, TNFα production from peripheral blood mononuclear cells was reduced during EEN (P = .008) and reached levels like healthy control subjects. In parallel to these changes, the fecal concentrations of acetate, butyrate, propionate, choline, and uracil significantly decreased in FC responders, and p-cresol significantly increased. At EEN completion, TNFα production from peripheral blood mononuclear cells was positively correlated with butyrate (rho = 0.70; P = .016). Microbiota structure (β diversity) was influenced by EEN treatment, and a total of 28 microbial taxa changed significantly in fecal calprotectin responders. At EEN completion, TNFα production positively correlated with the abundance of fiber fermenters from Lachnospiraceae_UCG-004 and Faecalibacterium prausnitzii and negatively with Hungatella and Eisenbergiella tayi. CONCLUSIONS: This study offers proof-of concept data to suggest that the efficacy of EEN may result from modulation of diet-dependent microbes and their products that cause inflammation in patients with CD.
Keywords: Gastrointestinal Microbiome; feces; Humans; dítě; Child; Female; Leukocytes, Mononuclear; Crohn Disease; Leukocyte L1 Antigen Complex; lidé; TNF-alfa; Feces; ženské pohlaví; Male; Adolescent; Crohnova nemoc; Enteral Nutrition; leukocyty mononukleární; Tumor Necrosis Factor-alpha; střevní mikroflóra; enterální výživa; mužské pohlaví; leukocytární L1-antigenní komplex; mladiství